The effects on milk marketing of cooperative partnership of dairy farmers: a case study from Türkiye - Can, Bahar Aydin; Engindeniz, Sait (Frontiers in Sustainable Food Systems, 2025)
In the agricultural sector, dairy cattle farming is a sector with a significant economic impact. One of Türkiye’s priority goals in agricultural development is to raise awareness of organization among farmers. Cooperatives play a crucial role in ensuring the sustainability of farmers in production. For dairy cattle farmers, one of the most effective means to market their milk is through cooperatives. The aim of this study is to reveal the socioeconomic characteristics, cooperative status and the effect of the cooperative on milk marketing of dairy cattle farmers who are members of the cooperative in Derince district of Kocaeli province. The main material of the study consisted of the data obtained by questionnaire method from 61 farmers who are members of Cavuslu Village Agricultural Development Cooperative in Derince district of Kocaeli province, Türkiye. The research includes data obtained during the 2020 production period. Dairy cattle farms were divided into 3 groups according to the presence of dairy cows and analyzed. Logistic regression analysis was used to determine the factors affecting the marketing of milk produced by the dairy cattle farms through cooperatives. According to the results of the research, 57.38% of the farmers market their milk through cooperatives. On average, there are 4.94 heads of domestic breed, 11.78 heads of culture breed and 9.20 heads of crossbred cows in the farms. The average milk selling price is 0.37 USD/kg. It was determined that the most effective factor for farmers to give milk to the cooperative was the selling price of milk. Dairy cattle farms with fewer milking cows and those without cooling tanks are more likely to sell their milk to the cooperative. In conclusion, for cooperatives to play a more effective role in dairy cattle farming, it is necessary to increase the competitiveness of cooperatives and ensure their effectiveness in the milk market through the establishment of processing and packaging facilities in the region.